Aristotle : his life and school - Natali, Carlo, 1948- (Princeton University Press, 2013)
This definitive biography shows that Aristotle's philosophy is best understood on the basis of a firm knowledge of his life and of the school he founded. First published in Italian, and now translated, updated, and expanded for English readers, this concise chronological narrative is the most authoritative account of Aristotle's life and his Lyceum available in any language. Gathering, distilling, and analyzing all the evidence and previous scholarship, Carlo Natali, one of the world's leading Aristotle scholars, provides a masterful synthesis that is accessible to students yet filled with.